Impact of Reverse Supply Chain on Bullwhip Effects in Beef Supply - Paduloh, Paduloh; Djatna, Taufik; Muslich, Muslich; Sukardi, Sukardi (ExcelingTech, 2020)
As a beef distributor company, the challenge of being able to balance demand and supply is very important, given the consumption and distribution patterns that are unstable and are influenced by the nature of meat that is perishable and requires special handling. The purpose of this study is to analyze the bullwhip effect that occurs in the beef industry, the level of inventory and forecasting beef. This research will calculate the level of bullwhip effect of the reverse supply chain beef with one distributor and three types of retailers and customers. The analysis is carried out on the demand pattern and shipping intensity of the customer distributors and analyses the effect of the reverse supply chain on the bullwhip effect. After the inventory formulation is obtained, the effect of the reverse supply chain on the beef bullwhip effect, then the best formulation for inventory forecasting using ARIMA is sought. In this research, a new formulation of inventory patterns is influenced by product returns and reverse supply chains. From the results of calculations using a new inventory formulation by including a reduction to replace the returned product, it appears that this condition affects the bullwhip effect where the company will consider the product as a sale when in fact it is a replacement. By this paper, we release a new reverse supply chain model in the beef industry to get value-added.